Evaluation of maximal isometric hand grip strength in different sports - Ajeet, J. E.; Singh Rajpurohit, V.; Ram Sharma, M.; Kumar Jadiya, M.; Choudhary, A. (Indian Journal of Physiotherapy and Occupational Therapy, 2021)
Background: Grip strength has proven to have a positive effect on sports performance in which a sport implement is grasped in the hand. Objective: To compare Hand Grip Strength in males of different sports. Materials and Methods: 400 male sportsmen, 100 in each sport (Cricket, Hockey, Tennis and Badminton) aged 18-25 yrs volunteered to participate in this study were engaged. Each participant was asked to perform at least three maximal isometric grip strength measurements using a Jamar Handgrip Dynamometer and the average of the three grip strength trials readings was recorded. Statistical analysis: R-Programming Language Software was applied for statistical analyses of the data; the results were statistically analyzed by ANOVA. Results: The findings of the present study showed that the maximum grip strength measured in both hands is higher in Cricket players than in Hockey, Tennis and Badminton players (P<0.05). Conclusion: In the present study hand grip strength might have increased due to regular training. It would be beneficial to the sportsmen in terms of optimizing training programs separately for particular sports.